Maruni Dance: A Cultural and Religious Jewel of the Magar Community in Indrasarowar Rural Municipality - Ghising, Tilak; Magar, Keshar Thapa (Journal of Indigenous Knowledge and Practice, 2025)
This study explores the Maruni dance within the Magar community of Indrasarowar Rural Municipality-02, Kiteni, Makawanpur district in the Bagmati Province, focusing on its historical, cultural, and religious significance. By examining the dance’s role in rituals, festivals, and community relationships, the research highlights the importance of Maruni in preserving cultural heritage. Utilizing a mixed method approach that includes surveys and interviews, the study identifies key challenges facing Maruni, such as the impact of modernization, generational shifts, and external cultural influences including urban migration and digital media. The findings reveal variations in the community’s perceptions of the dance’s relevance and future, with some aspects demonstrating higher levels of cultural attachment. Despite the influence of external factors, the dance remains an important symbol of Magar identity. The study concludes with suggestions for future research and policy implications to support the preservation of Maruni, addressing both cultural sustainability and contemporary challenges within the Magar community.